Wound Healing Activity of Evolvulus numularius Linn. - SAINI, V.; KINGER, H.K.; SHARMA, D.K.; AHUJA, N.; MIDDHA, A.; GUPTA, V.B. (Asian Journal of Chemistry, 2010)
The methanol and aqueous extract of the plant Evolvulus numularius Linn. (Convolvulaceae), were screened for wound healing property on excision, incision wound models in Wistar albino rats. Both the extract showed significant wound healing activity. However, the rats of wound contraction and epithelialization was faster in methanol extract groups.